Speech Classes During COVID-19 Pandemic: Challenges Faced by the Classroom Teachers: Louie P. Gula - . (PJDOL, 2022)
The research study aimed at assessing the various difficulties that speech teachers had in delivering lessons during the distance learning era. The various phenomena and themes that emerged from the survey were determined using a descriptive research design. The survey was conducted to collect information about the various characteristics and behavior of speech teachers. It also explored the factors that influenced their decisions and actions when it came to addressing the pandemic. The repeated themes that emerged, include low motivation, altered activities, unstable internet connection, comprehension, questionable output integrity, delayed submissions, in-person monitoring, and the system of communicating with inactive students in online mode.